Clinicoepidemiological Profile of Short Stature at A Tertiary Care Centre in Bangladesh (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Short stature (SS) is a common pediatric problem, which can cause psychosocial disturbances both in parents and children. The goal of the evaluation of a child with SS is to identify the subset of children with pathologic causes so that appropriate timely intervention can be made.Objective: The aim of the study was to study the clinical, epidemiological, and etiological profile of SS at a tertiary hospital of Bangladesh.Methods: This was a cross-sectional study and was conducted in the department of pediatric endocrinology, over a period of 1 year (January 2021-December 2021). A total of 100 children aged 3-14 years, with height